Transport Stress Induces Skin Innate Immunity Response in Hybrid Yellow Catfish (Tachysurus fulvidraco♀ × P. vachellii♂) Through TLR/NLR Signaling Pathways and Regulation of Mucus Secretion - Zheng, Tao; Song, Zhuo; Qiang, Jun; Tao, Yifan; Zhu, Haojun; Ma, Junlei; Xu, Pao (Frontiers in Immunology, 2021)
The transport of live fish is a necessary step for commercial production and for research. The skin of scaleless fish is the first non-specific immune barrier against exogenous stimuli, and it plays an important protective role under transport stress. Thus, the aim of this study was to explore the skin responses to transport stress in hybrid yellow catfish (Tachysurus fulvidraco♀ ×Pseudobagrus vachellii♂) through transcriptome and biochemical analyses. Water samples were collected during a simulated transport treatment. Biochemical indexes and/or gene expression in blood, skin, and mucus in fish in control groups and transport-stress groups (0 h, 2 h, 4 h, 8 h, 16 h) were assayed. The levels of total ammonia–nitrogen and nitrite–nitrogen in the water increased with increasing transport time. Comparison of skin transcriptomes between the control group and the group subjected to 16 h of transport revealed 1547 differentially expressed genes (868 up-regulated and 679 down-regulated). The results of the transcriptome analysis were validated by analyses of the expression levels of selected genes by qRT-PCR. The results indicated that the TLRs/NLRs signaling pathway mediated the skin’s immune response to transport stress: tlr9, mfn2, and ikbke were significantly up-regulated and nfkbia and map3k7cl were significantly down-regulated under transport stress. With increasing transport time, mucosal lysozyme activity and the immunoglobulin M content in skin mucus first increased and then decreased. The number of mucous cells peaked at 8 h of transport stress, and then decreased. The main cell types changed from Ⅱ and Ⅳ to Ⅰ, Ⅱ, Ⅲ, and Ⅳ. Similarly, the levels of red and white blood cells, hemoglobin, and hematocrit first increased and then decreased by 16 h of transport. Together, the results that the skin responds to transport stress by activating the immune signaling pathway and regulating mucus secretion. These findings have important biological significance for selecting strains that tolerate transport, as well as economic significance for optimizing the transport conditions for scaleless fish.